The Influence of Work Environment on The Interaction Between Motivation, Employee Performance, Compensation and Employee Job Satisfaction (Analysis on Multinational and Domestic Companies) - Chintya Salsabiela; Syaiful Rahman Soenaria; Anies Lastiati (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the effect of the work environment on the interaction between motivation, employee performance, compensation, employee job satisfaction by comparing multinational and domestic companies. Data was collected using questionnaires distributed to employees in multinational and domestic companies in the West Java and Jakarta regions. The results show that the work environment significantly strengthens the positive effect between motivation and employee job satisfaction by 0.42, and the work environment significantly strengthens the positive effect between compensation and employee job satisfaction by 0.03. The work environment functions as a moderator that strengthens the relationship between motivation and compensation with job satisfaction. When the work environment supports, whether through good social relationships, support from supervisors, or adequate facilities, the effect of motivation and compensation on job satisfaction becomes more significant. However, it was found that the relationship between employee performance and job satisfaction is not significant at 0.190, which could be influenced by other factors such as the compensation received or the improvement of career opportunities. Multinational companies tend to have modern facilities and offer better international training opportunities, while domestic companies emphasize family values and provide facilities that are not inferior to multinational companies. However, there is a significant difference between multinational and domestic companies in managing the work environment, with the statistical value comparison of 0.759 for multinational companies and 0.806 for domestic companies. This shows that, in this study, the work environment has a better impact on job satisfaction in domestic companies compared to multinational.